Pengaruh Disiplin Kerja Dan Pengawasan Kerja Terhadap Kinerja Karyawan : Survei Pada Bagian Sopir Bus PT. Primajasa Perdanaraya Utama - Pramadieta Herniwan; Barin Barlian; Kusuma Agdhi Rahwana (Journal of Management and Creative Business, 2023)
This study aims to determine work discipline and work supervision on the performance of employees of PT. Primajasa Perdanaraya Utama. In this study using a survey method with a quantitative approach. The data collected in the form of data is done by using a questionnaire technique. Data analysis used in this study used multiple linear regression analysis, correlation coefficient analysis, and coefficient of determination using SPSS version 26. The results show that work discipline and work supervision simultaneously and partially have a significant effect on employee performance.